2023
DOI: 10.1158/1538-7445.sabcs22-ot1-03-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT1-03-02: Efficacy and safety of SKB264 for previously treated metastatic triple negative breast cancer in Phase 2 study

Abstract: Background: The therapeutic options for patients (pts) with previously treated metastatic TNBC are limited compared with other breast cancer subtypes. SKB264 is an antibody drug conjugate (ADC) composed of an anti-TROP2 antibody coupled to the cytotoxic belotecan-derivative via a novel linker. Here, we present results from a Phase 2 expansion cohort for pts with mTNBC (NCT04152499). Methods: Pts with previously treated mTNBC were enrolled to receive SKB264 4 mg/kg Q2W or 5 mg/kg Q2W in a non-randomized fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the cohort of 59 patients with locally advanced or metastatic TNBC with high Trop-2 expression, the ORR was 62.5%, the mDOR was 11.5 months, the mPFS was 5.7 months, and the mOS was 14.6 months. 55 Another phase 1/2, single-arm, basket study (NCT04152499) showed SKB-264 achieved a 36.8% (N = 14) ORR and 89.5% (N = 34) DCR in treating HRþ/HER2-MBC patients. The mPFS was 11.1 months (95% CI, 5.4-13.1).…”
Section: Skb-264mentioning
confidence: 99%
“…In the cohort of 59 patients with locally advanced or metastatic TNBC with high Trop-2 expression, the ORR was 62.5%, the mDOR was 11.5 months, the mPFS was 5.7 months, and the mOS was 14.6 months. 55 Another phase 1/2, single-arm, basket study (NCT04152499) showed SKB-264 achieved a 36.8% (N = 14) ORR and 89.5% (N = 34) DCR in treating HRþ/HER2-MBC patients. The mPFS was 11.1 months (95% CI, 5.4-13.1).…”
Section: Skb-264mentioning
confidence: 99%